Geriatric Distal Femur Fractures Treated with Arthroplasty Are Associated with Lower Mortality but Greater Costs Compared with Open Reduction and Internal Fixation at 30 Days - Gwam, Chukwuweike U.; Harmody, Kristen Confroy; Luo, T. David; Rosas, Samuel; Plates, Johannes (The Journal of Knee Surgery, 2024)
Distal femur fractures (DFFs) are common injuries with significant morbidity. Surgical options include open reduction and internal fixation (ORIF) with plates and/or intramedullary devices or a distal femur endoprosthesis (distal femur replacement [DFR]). A paucity of studies exist that compare the two modalities. The present study utilized a 1:2 propensity score match to compare 30-day outcomes of geriatric patients with DFFs who underwent an ORIF or DFR. The National Surgical Quality Improvement Program data from 2008 to 2019 were utilized to identify all patients who sustained a DFF and underwent either ORIF or DFR. This yielded 3,197 patients who underwent an ORIF versus 121 patients who underwent a DFR. A final sample of 363 patients (242 patients with ORIF vs. 121 with DFR) was obtained after a 1:2 propensity score match. Costs were obtained from the National Inpatient Sample database using multiple regression analysis and validated with a 7:3 train-test algorithm. Independent samples t-tests and chi-square analysis were conducted to assess cost and outcome differences, respectively. Patients who received a DFR had higher transfusion rates than ORIF (p = 0.021) and higher mean inpatient hospital costs (p = 0.001). Subgroup analysis for patients 80 years of age or older revealed higher 30-day unplanned readmission (0 vs. 18.2%; p < 0.001) and 30-day mortality (0 vs. 18.2%; p < 0.001) rates for patients undergoing ORIF compared with DFR. The total number of DFR cases needed to prevent one ORIF-related 30-day mortality for DFR for patients 80 years of age was 6 (95% confidence interval: 3.02–19.9). The mean hospital costs associated with preventing one case of death within 30 days from operation by undergoing DFR compared with ORIF was $176,021.39. Our results demonstrate higher rates of transfusion and increased inpatient costs among the DFR cohort compared with ORIF. However, we demonstrate lower rates of mortality for patients 80 years and older who underwent DFR versus ORIF. Future studies randomized controlled trials are necessary to validate the results of this study.
Keywords: trauma; knee; DFR; ORIF